2008
DOI: 10.1007/s10194-008-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

Headache in an Italian pediatric emergency department

Abstract: The objective of this study was to assess epidemiology, diagnostic work-up, treatment and follow-up of children presenting to emergency department (ED) with headache. Records of visits for non-traumatic headache to the ED of a pediatric hospital over a period of 12 months were retrospectively reviewed. Headache center charts were analyzed one year after. Five-hundred and fifty patients (1% of all ED visits) were included. Spectrum of diagnoses was: primary headache (56.7%), with 9.6% of migraine; secondary hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
57
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 20 publications
12
57
2
2
Order By: Relevance
“…Similar results have been found in paediatric ED attendances, 1% of which were attributed by an Italian survey to headache [15]. Primary headache was again diagnosed in most cases (57%).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results have been found in paediatric ED attendances, 1% of which were attributed by an Italian survey to headache [15]. Primary headache was again diagnosed in most cases (57%).…”
Section: Introductionsupporting
confidence: 80%
“…Primary headache was again diagnosed in most cases (57%). However, over 90% of secondary headaches were caused by viral illnesses, and only 4% of children were in any immediate danger [15].…”
Section: Introductionmentioning
confidence: 99%
“…5 The American Academy of Neurology/Child Neurology Society practice parameter supports the use of neuroimaging in patients with recurrent headaches and abnormal neurologic examination findings, seizures, or a history of recent-onset severe headache or recent changes in the nature of the headache. 4 Multiple pediatric emergency department (ED) studies have tried to identify warning signs deserving further workup, [6][7][8][9][10] and 2 of the studies suggested that an occipital headache location signified intracranial pathology. 7,9 Other warning signs not addressed in the practice parameter included younger age, severe intensity, and an inability to describe the quality of the pain.…”
mentioning
confidence: 99%
“…ED diagnosis was confirmed in 74.6 % of cases. Most ED repeated visits (82.6 %) occurred in patients not referred to the headache center at discharge from the first ED visit [9].…”
Section: Primary Versus Secondary Headachesmentioning
confidence: 99%